(untitled) (Cambridge, England, 2017)
MINDSET, the multi-level course from the organisation that produces the IELTS test, develops students' English skills and leaves them fully prepared for test day. MINDSET from Cambridge gets you inside the IELTS test with a unique blend of print and online content. Topic-based units cover each of the four skills in turn, making it easy to find what you want. This Teacher's Book accompanies MINDSET Student's Book Level 1, targeting Band 5.5. Designed to help teachers feel more confident in the classroom, it clearly guides you through the test, providing clear links between activities and the test, a glossary of IELTS terms, alternative exercises and extension activities. Audio content can be downloaded using the code printed on the inside front cover.
Keywords: Tiếng Anh,English language; Kỳ thi, câu hỏi,vv..,Examinations, questions, etc